Students' Challenges and Strategies in Creating Mind Maps in The TEYL Course - Hustarna, Hustarna; Efriani, Nanda (Universitas Jambi, Magister Program of English Education Department, 2025)
This study aimed to identify the challenges students face when creating mind maps and to explain the strategies they use to address them. The study employed a descriptive, qualitative method, utilizing semi-structured interviews to collect the data. The participants were selected purposively, with twelve students from an English Study Program at a state university in Jambi who had taken the TEYL course and created mind maps. The data were analyzed using thematic analysis. The study's findings identified two main themes: The first is related to the students’ challenges in creating mind maps, including being unfamiliar with mind maps, requiring a significant amount of time to create an engaging one, having limited space on the mind map, problems in using devices and applications to create mind maps, and identifying relevant keywords for the material. Meanwhile, the second is related to the strategies the students used in creating mind maps including creating a digital mind map, using a convenient device and a secure application, using visual elements, preparing a plan, grouping the material on the mind map, designing an efficient mind map format, using curved branches, preparing a summary of the material to create the keywords, and searching for many references. These findings provide valuable insights into the practical challenges students encountered in visual learning tasks and highlight their adaptive strategies in overcoming these challenges, reflecting their creativity, resourcefulness, and digital literacy.